Enterprise resource planning system integration and its effects on relationship between lean practices and organisational performances: A conceptual framework - Mohammad Enamul Hoque (International Society for Development and Sustainability (ISDS), 2018)
In the competitive business, world manufacturers are under pressure, and they want to be more efficient in wastage reduction while fulfilling customers’ demand. Thus, with the aim of better performance, in this emerging situation, manufacturers are adopting multi-approaches even though systems are contradicting each other, like lean practices and Enterprise Resources Planning system. This study deliberates whether Enterprise Resources Planning system fits within a lean manufacturing environment. This study also develops a conceptual framework which can facilitate to investigate the role of Enterprise Resources Planning system integration on business performances within a lean manufacturing environment. The framework also shows that Enterprise Resources Planning system play are interactional roles on the relationship between lean practices and business performances, indicating the moderating effects of Enterprise Resources Planning system on their relations. This study also discusses the theoretical and managerial implications of the proposed framework. Finally, this study deliberates how the conceptual framework can be extended into empirical research.